Crossmodal links between audition and touch in covert endogenous spatial attention. - Lloyd, D; Merat, N; McGlone, F; Spence, C (2003)
We report three experiments designed to investigate the nature of any crossmodal links between audition and touch in sustained endogenous covert spatial attention, using the orthogonal spatial cuing paradigm. Participants discriminated the elevation (up vs. down) of auditory and tactile targets presented to either the left or the right of fixation. In Experiment 1, targets were expected on a particular side in just one modality; the results demonstrated that the participants could spatially shift their attention independently in both audition and touch. Experiment 2 demonstrated that when the participants were informed that targets were more likely to be on one side for both modalities, elevation judgments were faster on that side in both audition and touch. The participants were also able to "split" their auditory and tactile attention, albeit at some cost, when targets in the two modalities were expected on opposite sides. Similar results were also reported in Experiment 3 when participants adopted a crossed-hands posture, thus revealing that crossmodal links in audiotactile attention operate on a representation of space that is updated following posture change. These results are discussed in relation to previous findings regarding crossmodal links in audiovisual and visuotactile covert spatial attentional orienting.